Peranan Ormas Islam Dalam Penguatan Ekonomi Syariah Di Kepulauan Riau: Perspektif Aspek Ekonomi, Sosial Dan Budaya - Aslina, Neri -; Beddu, Muhammad Juni; Addieningrum, Fithri Mehdini; Azhari, Muhammad Iqbal; Nurlatifah, Nurlatifah (ITB AAS INDONESIA Surakarta, 2024)
This research aims to analyze the role of Islamic organizations in strengthening the sharia economy in the Riau Islands from the perspective of economic, social and cultural aspects. This research method uses qualitative research methods through case studies. The research results show that Islamic organizations have a very important role in strengthening the sharia economy in the Riau Islands region through studying economic, social and cultural perspectives. Islamic organizations are also involved in supervising regional financial management, which seeks to ensure transparency, accountability and efficient use of public budgets as well as providing financial management training and guidance to local communities, so as to increase the capacity to manage regional finances independently. This research provides a better understanding of the role of Islamic mass organizations in the Riau Islands from an economic, social and cultural perspective. It is hoped that the implications of this research can become a basis for local governments and Islamic organizations to increase efforts to implement sharia economics in the Riau Islands region.